The utility of the Upper Triassic conodont Primatella in Tethyan-Panthalassan correlation around the Carnian-Norian boundary - Orchard, Michael J. (Frontiers in Earth Science, 2023)
The Upper Triassic conodont genus Primatella is important for recognizing the Carnian-Norian stage boundary in Panthalassan and Tethyan domains. Originally based on Canadian material from Black Bear Ridge in the Western Canada Sedimentary Basin, two key species are highlighted, and their occurrence is documented in the allochthonous Wrangellia and Alexander terranes in the North American Cordillera; in the Great Basin in Nevada, western United States; at Pizzo Mondello, Sicily, in western Tethys; and in Timor-Leste on the southeastern margin of the Meso-Tethys Ocean (northeastern Gondwana). The correlation potential of Primatella species is compromised by a differing nomenclature employed in Tethyan regions of Europe where Primatella species have been assigned to other genera, namely, Ancyrogondolella (formerly Epigondolella), Carnepigondolella, and Metapolygnathus. This has obscured phyletic relationships and impacted the stratigraphic utility of two demonstrably cosmopolitan species, P. asymmetrica and P. bifida. These species are shown to occur widely in a variety of paleoenvironments and have a restricted stratigraphic range around the CNB for which they can be adopted as useful indices.